China-Myanmar Relations Since Naypyidaw’s Political Transition: How Beijing Can Balance Short-Term Interests And Long-Term Values - Li, Chenyang (2016)
In discussions on Myanmar's political reforms since the installation of a civilianised military regime in 2011, most analysts have focused on the bedevilment of bilateral ties between Beijing and Naypyidaw. To be sure, China has since become more attuned to the concerns of non-state actors with the opening up of Myanmar's political space as well as recalibrated its strategies in the face of renewed diplomatic competition from other countries in vying for the affections of the Burmese leadership. In acknowledging the corrections China‘s Myanmar policy has undergone, this article argues that Beijing‘s factoring in of Burmese national interests and development needs can help enhance its prospects. While a return to the previous robust bilateral relationship may appear inconceivable in the near future, this article concludes that there is still hope for Beijing in overcoming the challenges posed by Naypyidaw's political transition should it be able to keep up with the latter's evolution over the longer term.